Pineapple peel: its million benefits / Deni Novia - Novia, Deni (UiTM Cawangan Negeri Sembilan, 2022)
Recently, global fruit production kept exhibit steadily increasing point. In 2020, not less than 887 million metric tons of fresh fruits worldwide production was recorded (www.statista.com). As generally known, fruit is a great source of vitamins, minerals, antioxidants, fiber and water but it generally lows in calories, making it an ideal source for appetizer or dessert. Consuming fruit every day will have a positive impact on health; otherwise, a lack of fruit will trigger several dangerous diseases. Some fruits could be consumed directly with negligible by- products; while some others might produce significant unconsumed materials because they should be peel or cover removal before eating. The fruit peel in large enough quantities might considered as disposed waste and even as a source of new problems that will pollute the environment, cause unpleasant odors, produce methane which will cause global warming/greenhouse effect and cause several health problems. Have you ever thought about using fruit peels from our consumption at home to be useful, or even provide a million benefits? Pineapple that structurally divided into flesh, crown, and peel is one of later fruit mentioned. Pineapple peel contains chemicals such as flavonoids, tannins, and saponins which its antibacterial benefits. The research of Romelle et al. (2016) found that pineapple peel contains 5.11% crude protein, 5.31% fat, 4.39% ash, 14.80% crude fiber, 55.52% carbohydrates, minerals Ca 8.30, Zn 6.46, Fe 25.52, and Mn 5.32 mg/100g. Anti-nutritional substances found in the peel are still safe for consumption, namely oxalates content 129.06mg %, hydrogen cyanides content 71.50mg %, alkaloids content 16.19%, phytates 1.99%, and total phenolics 1.42% (dry basis). It could be highlighted that pineapple peel can be used as a good ingredient in the formulation of food products due to its health benefit.